Determinação da área de inundação da bacia hidrográfica do rio Butuí, oeste do RS, a partir de técnicas de sensoriamento remoto - Piegas, Maria Eugênia Figueiredo (2021)
Having knowledge of the behavior of water bodies in times of high precipitation is of fundamental importance in order to avoid loss of human life and financial losses. Therefore, remote sensing techniques offer important resources for mapping water resources and also for monitoring surface water dynamics. The main objective of this work was to determine the area effectively flooded in the Butuí River Hydrographic Basin, applying different spectral indices, considering the extreme event that occurred in 2017 as a parameter. June 2016 and June 11, 2017 for the calculation and comparison of indices (NDVI, NDWI, NDPI and MNDWI). It was possible to verify that the NDVI index presented a value of effectively flooded area different from the other indexes, showing that this index is not suitable for this type of research. The NDPI and MNDWI indices present values of effectively flooded area very close, showing that this technique is efficient for the search, using the appropriate indices.